1991
DOI: 10.3109/00365549109024303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types and Combinations of Antimicrobial Agents on Endotoxin Release from Gram-negative Bacteria: An In-Vitro and In-Vivo Study

Abstract: Total and free endotoxin release in time from cultures of Escherichia coli by different antibiotics was studied in vitro for 4 h in relation to the antibiotic effect on viable counts and morphological features of the test cultures. The most rapid fall in viable counts was seen after treatment with imipenem or the combination of imipenem with tobramycin, accompanied by an early, but minimal increase (1.8-fold) of the total (free plus cell-bound) endotoxin level at 1 h. Total endotoxin levels increased approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
2
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 19 publications
11
120
2
3
Order By: Relevance
“…Since LPS associates with circulating lipoproteins (54), is rapidly cleared by the reticuloendothelial system (55), and nonspecifically inserts itself into lipid membranes, these levels may understate the levels of LPS presented to the host. LPS is continuously shed from the outer membranes of rapidly proliferating bacteria, and this release can be further increased up to Ïł200-fold through antibiotic-induced bacterial lysis (56,57). During endotoxemia, the endothelium responds not only to LPS itself but, simultaneously, to numerous endogenous mediators, such as TNF-␣, interleukin (IL)-1␀, interferons, and others (8 -10).…”
Section: Discussionmentioning
confidence: 99%
“…Since LPS associates with circulating lipoproteins (54), is rapidly cleared by the reticuloendothelial system (55), and nonspecifically inserts itself into lipid membranes, these levels may understate the levels of LPS presented to the host. LPS is continuously shed from the outer membranes of rapidly proliferating bacteria, and this release can be further increased up to Ïł200-fold through antibiotic-induced bacterial lysis (56,57). During endotoxemia, the endothelium responds not only to LPS itself but, simultaneously, to numerous endogenous mediators, such as TNF-␣, interleukin (IL)-1␀, interferons, and others (8 -10).…”
Section: Discussionmentioning
confidence: 99%
“…5). Dofferhoff et al (1991) and Jackson et al (1992) have reported the effects of antibiotic treatment on the release of endotoxin by gram-negative bacteria. They have reported that the high levels of endotoxin with treatment with b-lactamase inhibitors of cephem antibiotics are the result of the formation of long filaments with late lysis, because these antibiotics bind to both penicillin-binding proteins (PBP)-1 and PBP-3 and produce lysis as well as filamentous changes.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the samples form a gel phase at 25 and 35 8C and a lamellar liquid crystalline (L a ) phase at 45 and 55 8C (see below). 31 P NMR spectra recorded from samples with water contents of 50, 70, 90, and 95% (w/w) also indicate that a transition between a gel phase and an L a phase occurs between approximately 35 8C and 45 8C. In addition, these spectra exhibit two narrow signals which originate from lipid aggregates undergoing isotropic motional averaging (Fig.…”
Section: Physico-chemical Properties Of Mfgl-iimentioning
confidence: 86%
“…31 P NMR spectra were obtained at 162.13 MHz using a Hahn echo pulse sequence with extended phase cycling [12]. Protons were decoupled during the data acquisition using the WALTZ decoupling scheme [13].…”
Section: Nmr Measurementsmentioning
confidence: 99%